Green-Synthesized Nanomaterials for Aflatoxin Mitigation: A Review - Gelaye Y; Luo H (Nanotechnology, Science and Applications)
Yohannes Gelaye,1,2 Huaiyong Luo1 1Key Laboratory of Biology and Genetic Improvement of Oil Crops, Ministry of Agriculture, Oil Crops Research Institute of the Chinese Academy of Agricultural Sciences (CAAS), Wuhan, 430062, People’s Republic of China; 2Department of Horticulture, College of Agriculture and Natural Resources, Debre Markos University, Debre Markos, EthiopiaCorrespondence: Huaiyong Luo, Email huaiyongluo@caas.cnAbstract: Aflatoxin contamination poses a significant challenge to global food safety, public health, and agricultural sustainability. Traditional methods for mitigating aflatoxins, such as chemical and physical detoxification techniques, often raise concerns about environmental harm, nutrient loss, and potential toxicity. In contrast, green-synthesized nanomaterials have emerged as an environmentally friendly and effective solution for controlling aflatoxins. This study explores the potential of green-synthesized nanomaterials for aflatoxin mitigation, focusing on their mechanisms of action, effectiveness, and long-term applicability in agricultural and food safety contexts. A comprehensive review of 116 articles on the latest developments in green nanotechnology was used, focusing on the creation, characterization, and application of nanoparticles, including silver, zinc oxide, titanium dioxide, and iron-based nanomaterials. Green nanoparticles reduce aflatoxin load primarily through their antioxidant properties, which neutralize oxidative stress, and their high adsorption capacity, which binds aflatoxins and reduces their bioavailability. Photocatalytic degradation, adsorption, and enzymatic detoxification were also evaluated. The results indicate that green-synthesized nanoparticles exhibit high efficacy, biocompatibility, and minimal environmental impact, especially when compared to traditional detoxification methods. However, challenges such as nanoparticle stability, large-scale production, regulatory issues, and potential long-term toxicity still require further investigation. To advance this field, future studies should focus on refining green synthesis processes, enhancing nanoparticle stability, and exploring the integration of nanotechnology with biosensors and smart packaging for real-time aflatoxin monitoring. By advancing these sustainable technologies, this research aims to contribute to the development of effective and safe methods for aflatoxin mitigation, thereby supporting global food security, public health, and environmental sustainability.Plain Language Summary: Aflatoxins are toxic substances produced by certain fungi, mainly Aspergillus species. These toxins contaminate food and animal feed, posing serious health risks and economic losses. Traditional methods to control aflatoxins, such as chemical treatments and pesticides, can be harmful to human health and the environment. Physical techniques like sorting, washing, and milling are not always effective. Researchers wanted to explore safer and more effective solutions.Scientists investigated nanomaterials-tiny particles that can interact with aflatoxins in new ways, and they focused on three eco-friendly types:Silver nanoparticles (AgNPs)Zinc oxide nanoparticles (ZnO NPs)Carbon-based nanomaterialsThese materials showed great potential for reducing aflatoxins by:Breaking down (degrading) 60-90% of the toxinsTrapping (adsorbing) 50-80% of aflatoxinsStopping fungal growth by 70-90%The study also examined eco-friendly coatings made from nanomaterials, and these coatings:Reduced Aspergillus fungi by 60-80%Helped food stay fresh 5 to 15 days longerThus, nanomaterials offer a promising, natural way to control aflatoxin contamination. Unlike traditional methods, they are safer for people and the environment. Using these materials could lead to healthier food, less waste, and better protection for farmers and consumers. More research and development could help bring these solutions to farms and food industries worldwide.Keywords: adsorption, degradation, green synthesis, microorganisms, nanomaterial